Non-Parallel-Flow Effect on Compressible Boundary Layer on a Flat Plate. (2015) - Huang, Zhangfeng; Wu, Xuesong
Abstract: Instability of boundary layers is an important aspect of laminar flow - turbulence transition. A local, simple and non-perturbative approach to spatial instability of three-dimensional compressible boundary layers, referred to as 'extended eigenvalue' or 'EEV' approach, is presented, in which both the streamwise variation of the mean flow and the shape distortion of the disturbance are taken into account. In the case of compressible Blasius boundary layer on a flat plate, the predictions are verified and confirmed by direct numerical simulation results, and the non-parallel effects on eigenvalues, eigenfunctions and neutral curves for different Mach numbers are discussed.